Cancer incidence and mortality in a historical cohort of Australian pest control workers. Issue 12 (23rd June 2009) - MacFarlane, E; Benke, G; Del Monaco, A; Sim, M R
Abstract : Objectives: To determine the rates of mortality and incident cancer in a historical cohort of pest control operators. Methods: A retrospective cohort was assembled from former state government occupational health surveillance programmes. This cohort was linked to the Australian national registries of cancer and mortality and the results were compared with the general Australian population rates. Results: 125 deaths and 89 incident cancers were found during the periods of observation (mortality 1983–2004 and cancer 1983–2002). Overall cancer incidence and mortality rates were not found to be significantly different from the general population. Among the specific causes of death, suicide (standardised mortality ratio; SMR 1.78; 95% CI 1.12 to 2.83) and unintentional falls (SMR 4.57; 95% CI 1.72 to 12.19) were significantly in excess, although the latter was based on only 4 deaths. Melanoma was the only specific incident cancer found significantly in excess (standardised incidence ratio 1.56; 95% CI 1.03 to 2.37). Conclusions: Pest control workers have overall mortality and cancer rates similar to the general population. Excess rates of incident melanoma and intentional self-poisoning mortality are of concern and warrant further investigation. Follow-up of this cohort as its members age, will provide more insight into these possible associations.